Application of the Sydney System for Classification and Reporting Lymph Node Cytopathology to Assess the Risk of Malignancy and its Diagnostic Accuracy - Sudipta Das; Aseema Das; Bandita Das (Journal of Cytology)
Background: Fine-needle aspiration cytology (FNAC) of the lymph nodes is the first-line evaluation of lymphadenopathy of unknown etiology. For better diagnostic clarity and proper communication to clinicians, the Sydney System was proposed in 2020 for the performance, classification, and reporting of lymph node cytopathology. The present study was conducted to analyze the diagnostic performance and risk of malignancy (ROM) associated with each of the diagnostic categories of the proposed Sydney System. Materials and Methods: This retrospective study was conducted over 2 years. All patients with lymphadenopathy undergoing FNAC during the study period for which subsequent histopathological examination (HPE) reports or clinical follow-up data were available were included in the study. The original diagnoses were reviewed, and each case was assessed according to the first diagnostic level of the Sydney System classification. The diagnostic accuracy and ROM were correlated with FNAC diagnoses. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of lymph node FNAC were calculated using SPSS version 20.0. Results: A total of 456 out of 753 cases were selected in the study as they had subsequent histopathological correlation and/or clinical follow-up data. The majority were females n = 294 (64.4%). The most common lymph node was the cervical group (n = 274, 60%). On Statistical Analysis: sensitivity 82.8%, specificity 97.5%, PPV 95.3%, NPV 90.1%, and diagnostic accuracy 92%. Conclusion: The sydney system, which introduces a uniform categorization, may increase the lymph node FNAC diagnostic accuracy.